Comment on: Teaching Neuroimages: Hypometabolism of the primary motor cortex in primary lateral sclerosis: The stripe sign. - Turner, M; Cosgrove, J; Jamieson, S; Chowdhury, F (American Academy of Neurology, 2016)
Commenting on “Teaching NeuroImages: Hypometabolism of the primary motor cortex in primary lateral sclerosis: The stripe sign,” Dr. Turner proposes that when primary lateral sclerosis (PLS) symptoms start in the upper extremity, the disease invariably progresses to amyotrophic lateral sclerosis.